2017
DOI: 10.1098/rsos.160559
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between stimulus contrast and pre-saccadic crowding

Abstract: Objects that are briefly flashed around the time of saccades are mislocalized. Previously, robust interactions between saccadic perceptual distortions and stimulus contrast have been reported. It is also known that crowding depends on the contrast of the target and flankers. Here, we investigated how stimulus contrast and crowding interact with pre-saccadic perception. We asked observers to report the orientation of a tilted Gabor presented in the periphery, with or without four flanking vertically oriented Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…For example, those authors reported that pre-saccadic enhancement in performance was found also for un-flanked letter targets followed by a mask, consistent with a temporal rather than a spatial effect. Moreover, in a similar experiment to Harrison et al [ 27 ], Ağaoğlu and Chung [ 38 ] reported that during the pre-saccadic period the level of crowding was not in fact reduced compared to a fixation condition when different combination of high/low contrast target/flanker stimuli were used. On the contrary, saccades actually made crowding worse in some of the conditions tested.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…For example, those authors reported that pre-saccadic enhancement in performance was found also for un-flanked letter targets followed by a mask, consistent with a temporal rather than a spatial effect. Moreover, in a similar experiment to Harrison et al [ 27 ], Ağaoğlu and Chung [ 38 ] reported that during the pre-saccadic period the level of crowding was not in fact reduced compared to a fixation condition when different combination of high/low contrast target/flanker stimuli were used. On the contrary, saccades actually made crowding worse in some of the conditions tested.…”
Section: Introductionmentioning
confidence: 74%
“…The first main finding was to confirm that masking did indeed have a strong effect on orientation discrimination performance in this task. This was important in order to confirm the idea that the main influence of saccades on performance are primarily due to un-masking rather than un-crowding [ 36 ], [ 37 ], [ 38 ]. Second, we found a general pre-saccadic improvement in performance (significant in 4 out of 6 conditions) that was present already quite early and remained constant throughout the time course of the pre-saccadic time period.…”
Section: Experiments 1: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinematic properties of visual actions might also contribute to spatial perception. Evidence for this potential link comes from trans-saccadic localization and the study of crowding [152][153][154][155] , a bustling domain of vision research that, with few exceptions [156][157][158][159][160] , studies peripheral vision exclusively during visual fixation.…”
Section: Spatial Processingmentioning
confidence: 99%